Use of general practice, diagnostic investigations and hospital services before and after cancer diagnosis - a population-based nationwide registry study of 127,000 incident adult cancer patients - Christensen Karina; Fenger-Grøn Morten; Flarup Kaare; Vedsted Peter (BMC, 2012)
Abstract Background Knowledge of patterns in cancer patients' health care utilisation around the time of diagnosis may guide health care resource allocation and provide important insights into this groups' demand for health care services. The health care need of patients with comorbid conditions far exceeds the oncology capacity and it is therefore important to elucidate the role of both primary and secondary care. The aim of this paper is to describe the use of health care services amongst incident cancer patients in Denmark one year before and one year after cancer diagnosis. Methods The present study is a national population-based case-control (1:10) registry study. All incident cancer patients (n = 127,210) diagnosed between 2001 and 2006 aged 40 years or older were identified in the Danish Cancer Registry. Data from national health registries were provided for all cancer patients and for 1,272,100 controls. Monthly consultation frequencies, monthly proportions of persons receiving health services and three-month incidence rate ratios for one year before and one year after the cancer diagnosis were calculated. Data were analysed separately for women and men. Results Three months before their diagnosis, cancer patients had twice as many general practitioner (GP) consultations, ten to eleven times more diagnostic investigations and five times more hospital contacts than the reference population. The demand for GP services peaked one month before diagnosis, the demand for diagnostic investigations one month after diagnosis and the number of hospital contacts three months after diagnosis. The proportion of cancer patients receiving each of these three types of health services remained more than 10% above that of the reference population from two months before diagnosis until the end of the study period. Conclusions Cancer patients' health service utilisation rose dramatically three months before their diagnosis. This increase applied to all services in general throughout the first year after diagnosis and to the patients' use of hospital contacts in particular. Cancer patients' heightened demand for GP services one year after their diagnosis highlights the importance of close coordination and communication between the primary and the secondary healthcare sector.